A dihedral-angle-controlled mechanochromic luminescent material: Application for pressure sensing. (September 2020) - Hou, Yue; Li, Yue; Zhang, Mengyao; Zhang, Xunxue; Xu, Zhenzhen; Li, Yaping; Duan, Yuai; Han, Tianyu
Abstract: For most of the mechanochromic luminescent (MCL) materials, their mechanisms are based on the phase transition. When they are fabricated into devices or films, the MCL cannot be fully activated due to uncontrollable phase state of the materials. In this study, a new MCL material, ( E )-6-chloro-N-(4-(dimethylamino)benzylidene)benzo[ d ]thiazol-2-amine (CDBTA ), functioning based on dihedral-angle change, was reported. The initial state of CDBTA glows green emission (520 nm), while grinding changes its colour into yellow-orange (551 nm). The switching between two emission states can be stably switched with high fatigue resistance. The underlying MCL mechanism was verified by crystal analyses on two forms of single crystal, namely Green-form (G-form) and Yellow-form (Y-form), respectively. Molecules in G-form crystal adopt the twisted conformation by the rotation of the donor-acceptor (D-A) biplane. The dihedral angle is thus fixed by a variety of intermolecular interactions. Under mechanical stimuli, these interactions are destructed and the intramolecular torsional stress is released. Thus the molecules cannot maintain twisted conformation but form D-A coplane similar to the Y-form. Such dihedral-angle-controlled structural relaxation makes the π-electron highly delocalized to facilitate bathochromic-shift. The MCL stems from the changes of dihedral angle of the D-A biplane rather than that in packing mode or phase state, therefore CDBTA offers the possibility to fully activate the MCL performances when instrumented. Encouraged by this advantage, a CDBTA film sensor for pressure detection was fabricated, which exhibits a gradual red-shift with pressure and low detection limit down to 15.21 MPa. Graphical abstract: Image 1 Highlights: A new mechanochromic material with aggregation-induced emission is presented. A dihedral-angle-controlled mechanism was proposed based on two forms of crystal. A quantitative pressure sensor with high sensitivity is developed.